KEMAMPUAN KOMUNIKASI ANAK TUNARUNGU - Totok Bintoro (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
This research aimed to find out the influencing differences of variables such as learning strategies and levels of deafness toward the verbal and non verbal communication ability in hearing impairment children. Besides, this research also aimed to find out whether there are interactions between two independent variables or not that influence verbal and nonverbal communication ability in hearing impairment children. For those purposes, an ex post facto comparative research was conducted to compare the influence of MMR learning strategies and conventional learning strategies that had been done at Special Needs Elementary School for Hearing Impairment Children by noticing the levels of deafness (hard of hearing and deaf) toward verbal and nonverbal communication ability. In the line of the problems,this research used a factorial design 2x2 to respond the verbal, nonverbal, and combination of verbal and nonverbal communication ability. The results of this research are (1) overall, hearing impairment children classified as hard of hearing and deaf who study by using MMR learning strategy have higher communication (verbal and nonverbal) ability than those who study by using learning strategy conventionally; (2) overall, based on the levels of deafness, hearing impairment children classified as hard of hearing have higher communication ability than hearing impairment children classified as deaf; (3) there are interaction influences between the learning strategies and levels of deafness toward communication ability in hearing impairment children.